Deglacial to Holocene variability in surface water characteristics and major floods in the Beaufort Sea - Wu, Junjie; Stein, Ruediger; Fahl, Kirsten; Syring, Nicole; Nam, Seung-Il; Hefter, Jens; Mollenhauer, Gesine; Geibert, Walter; Alfred Wegener Institute Helmholtz Centre for Polar and Marine Research, Bremerhaven, Germany; MARUM—Center for Marine Environmental Sciences, University of Bremen, Bremen, Germany; Korea Polar Research Institute, Incheon, Republic of Korea (Communications Earth & Environment, 2020)
Surface water characteristics of the Beaufort Sea have global climate implications during the last deglaciation and the Holocene, as (1) sea ice is a critical component of the climate system and (2) Laurentide Ice Sheet meltwater discharges via the Mackenzie River to the Arctic Ocean and further, to its outflow near the deep-water source area of the Atlantic Meridional Overturning Circulation. Here we present high-resolution biomarker records from the southern Beaufort Sea. Multi-proxy biomarker reconstruction suggests that the southern Beaufort Sea was nearly ice-free during the deglacial to Holocene transition, and a seasonal sea-ice cover developed during the mid-late Holocene. Superimposed on the long-term change, two events of high sediment flux were documented at ca. 13 and 11 kyr BP, respectively. The first event can be attributed to the Younger Dryas flood and the second event is likely related to a second flood and/or coastal erosion. The Beaufort Sea was nearly ice-free during the transition from the last deglacial to the Holocene, a period in which two episodes of high sediment flux suggest major glacial flood events, according to high-resolution multi-proxy biomarker records. Alfred Wegener Institute Helmholtz Centre for Polar and Marine Research (Alfred-Wegener- Institute, Helmholtz Centre for Polar and Marine Research) https://doi.org/10.13039/501100003207 China Scholarship Council (CSC) https://doi.org/10.13039/501100004543 National Research Foundation of Korea (NRF) https://doi.org/10.13039/501100003725